Sustainable Environment for Elderly People - Georgiev, Georgi Nikolov (Journal of Economic Development, Environment and People, 2019)
The paper is focused on extremely important issue of an aging population and the related need to explore, develop and extend prospective forms of sustainable environment for the elderly. Having in mind the persisting grow of ageing population the task is getting extremely large economic and social effect. Prospective trends in development of manmade environment for elderly people and their relevance to the Bulgarian situation are investigated. The relevance was considered from several points of view – economic, climatic, socio-cultural etc. Selected diploma projects of architecture students from NBU are outlined as good practice examples.